Editorial II DAT Meeting + Dossier PPGDesign UFCG - Prado, Gilbertto; Nesteriuk, Sérgio; Venturelli, Suzete; Ferreira da Silva, Itamar; Gomes de Medeiros, Wellington (DAT Journal, 2021)
In this issue of the DATJournal, in addition to the texts selected regularly by the journal, we have 2 dossiers. The first of them, with invited editors Gilbertto Prado, Sérgio Nesteriuk and Suzete Venturelli, we bring you some selected texts from the II DAT Meeting - Design, Art and Technology 2020. The edition of this DAT Meeting took place as part of the HUB events 2020, together with a consortium formed with three other events: VII SIIMI - International Symposium on Innovation in Interactive Media, # 19.ART - International Meeting of Art and Technology, II International Retina Colloquium.